Can intracranial time-of-flight-MR angiography predict extracranial carotid artery stenosis? - Osmanodja, Filiz; Scheitz, Jan F.; Fiebach, Jochen B.; Ganeshan, Ramanan; Villringer, Kersten (Journal of Neurology, 2021)
Objectives Extracranial stenosis of the internal carotid artery (ICA) is an important cause of ischemic stroke and transient ischemic attack (TIA). It can be diagnosed using contrast-enhanced CT or MR angiography (MRA) as well as Doppler ultrasound. In this study, we assessed the diagnostic value of intracranial time-of-flight (TOF) MRA to predict extracranial ICA stenosis (ICAS). Methods We retrospectively analyzed consecutive patients with acute ischemic stroke or TIA and middle- (50-69%) or high-grade (70-99%) unilateral extracranial ICAS according to NASCET criteria assessed by ultrasound between January 2016 and August 2018. The control group consisted of patients without extracranial ICAS. Intraluminal signal intensities (SI) of the intracranial ICA on the side of the extracranial stenosis were compared to the contralesional side on TOF-MRA source images. SI ratios (SIR) of contralesional:lesional side were compared between groups. Results In total, 151 patients were included in the main analysis. Contralesional:lesional SIR in the intracranial C4-segment was significantly higher in patients with ipsilateral extracranial ICA stenosis (n = 51, median 74 years, 57% male) compared to the control group (n = 100, median 68 years, 48% male). Mean SIR was 1.463 vs. 1.035 (p < 0.001) for right-sided stenosis and 1.362 vs. 1.000 (p < 0.001) for left-sided stenosis. Receiver-operating characteristic curve demonstrated a cut-off value of 1.086 for right-sided [sensitivity/specificity 75%/81%; area under the curve (AUC) 0.81] and 1.104 for left-sided stenosis (sensitivity/specificity 70%/84%; AUC 0.80) in C4 as a good predictor for high-grade extracranial ICAS. Conclusions SIR on TOF-MRA can be a marker of extracranial ICAS.
CRIS-Team WoS Importer:2021-11-19

Diagnostic Performance of 0.55 T MRI for Intracranial Aneurysm Detection - Osmanodja, Filiz; Rösch, Julie; Knott, Michael; Dörfler, Arnd; Grodzki, David; Uder, Michael; Heiß, Rafael (Investigative Radiology, 2023)
OBJECTIVES: Intracranial aneurysm (IA) is the main cause of subarachnoid hemorrhages. Time-of-flight (TOF) magnetic resonance angiography (MRA) at 1.5 T or 3 T magnetic resonance imaging (MRI) is a well-established method for the diagnosis of IA. The aim of this prospective study was to evaluate the performance of a modern 0.55 T MRI in the diagnosis of IAs in comparison to digital subtraction angiography (DSA) as a standard of reference. MATERIALS AND METHODS: Seventeen patients with suspicion of single or multiple IAs underwent TOF MRA at 0.55 T MRI 1 day before DSA. Two neuroradiologists independently measured the aneurysm neck, width, and height on 0.55 T, 1.5 T, and 3 T 3D-TOF MRA source images and 2D/3D rotational angiography. The main analysis assessed the intermodality agreement between 0.55 T TOF MRA and DSA using Bland-Altman plots, a Wilcoxon test, and the intraclass correlation coefficient (ICC). In a secondary analysis, aneurysm dimensions were compared between 0.55 T TOF MRA and 1.5/3 T TOF MRA. Interreader agreement was evaluated by ICC. A third neuroradiologist blinded to patient history screened 0.55 T TOF MRA data sets of the aforementioned 17 patients and 15 additional healthy patients for the presence and location of aneurysms. RESULTS: A total of 19 aneurysms in 16 patients were identified in both 0.55 T MRA and DSA. Measurements of the 2 nonblinded readers showed no significant differences between 0.55 T TOF MRA and DSA in the overall aneurysm size (calculated as the mean from height/width/neck) ( P = 0.178), as well as in the mean width ( P = 0.778) and neck values ( P = 0.190). The mean height was significantly larger in 0.55 T TOF MRA in comparison to DSA ( P = 0.020). Intermodality (1.5/3 T TOF MRA) and interrater agreement were excellent (ICC > 0.94). Of the 32 data sets of patients with and without IA, the blinded reader detected all aneurysms correctly by using 0.55 T images. CONCLUSIONS: TOF-MRA acquired with a modern 0.55 T MRI is a reliable tool for the detection and initial assessment of IAs.
CRIS-Team Scopus Importer:2023-01-20